2018
DOI: 10.1007/s00394-018-1874-z
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea drinking in relation to the risk of differentiated thyroid carcinoma: results from the European Prospective Investigation into Cancer and Nutrition (EPIC) study

Abstract: Purpose Coffee and tea constituents have shown several anti-carcinogenic activities in cellular and animal studies, including against thyroid cancer (TC). However, epidemiological evidence is still limited and inconsistent. Therefore, we aimed to investigate this association in a large prospective study. Methods The study was conducted in the EPIC (European Prospective Investigation into Cancer and Nutrition) cohort, which included 476,108 adult men and women. Coffee and tea intakes were assessed through val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
2
17
2
Order By: Relevance
“…However, this was probably due to their high content in sugar, 21 and not due to their high content in flavanones, 24 as diabetes is a probable risk factor of TC. 25 In the present study, a diet high in anthocyanidins and theaflavins and low in hydroxycinnamic acids, alkylmethoxyphenols and methoxyphenols was related to a decreased follicular TC risk using the quartiles of exposure, but they were not consistent with the results using the continuous variable or after the Bonferroni correction. 10 In the current study, no associations were observed with phenolic acids, lignans, stilbenes and other minor polyphenol subclasses.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…However, this was probably due to their high content in sugar, 21 and not due to their high content in flavanones, 24 as diabetes is a probable risk factor of TC. 25 In the present study, a diet high in anthocyanidins and theaflavins and low in hydroxycinnamic acids, alkylmethoxyphenols and methoxyphenols was related to a decreased follicular TC risk using the quartiles of exposure, but they were not consistent with the results using the continuous variable or after the Bonferroni correction. 10 In the current study, no associations were observed with phenolic acids, lignans, stilbenes and other minor polyphenol subclasses.…”
Section: Discussioncontrasting
confidence: 96%
“…10 In our study, we did not find any association with flavan-3-ol monomers. This null finding is in line with the lack of associations in EPIC between TC risk and intakes of any fruit group 24 or tea, 25 which are the main food sources of flavan-3-ol monomers. 11 In the NIH-AARP Diet and Health Study, a significantly positive association between flavanone intake and TC risk Cox model was stratified by sex, age and center, and additionally adjusted for smoking status, education level, body mass index (kg/m 2 ), physical activity, total energy intake (kcal/d) and alcohol (g/d) intakes and in women also for menopausal status, oral contraceptive use and infertility problems.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations